Սիրիայում ուղղիչ շարժման սոցիալ–տնտեսական քաղաքականության որոշ առանձնահատկությունները (1970-ական թթ.) - Ղարիբջանյան, Գևորգ («Զանգակ - 97»)
On November 1970 the Corrective Movement of Syria led by Hafiz al-Assad significantly changed nol only ihe internal and foreign affairs of the State, but also the muin dircclions of socio-economic policy.
Keywords: Պատմություն; Քաղաքականություն